Effect of thermal boundary conditions on dynamic characteristics of multi-lobed bearings. (June 2022) - Peixoto, Thales Freitas; Alves, Diogo Stuani; Tuckmantel, Felipe Wenzel da Silva; Daniel, Gregory Bregion; Machado, Tiago Henrique; Cavalca, Katia Lucchesi
Highlights: Three-dimensional thermo-hydrodynamic model of multi-lobed bearings. Effect of thermal boundary conditions on equivalent dynamic coefficients. Shaft and bush may be considered as isothermal or adiabatic. Higher oil film temperatures lead to smaller stiffness and damping coefficients. If shaft and bush are isothermal/adiabatic, temperature increase is smaller/higher. Abstract: This work presents a three-dimensional, variable viscosity, thermo-hydrodynamic model of multi-lobed journal bearings, capable to estimate the pressure and temperature distributions of the lubricant flowing between a rotating shaft and the partial arcs composing the multi-lobed bearing configuration, that must support the external applied load. The thermal model estimates the lubricant temperature increase and its effect on the pressure distribution, the bearing hydrodynamic forces and its equivalent stiffness and damping coefficients. Estimation of the temperature increase requires numerical solution of the energy equation, which depends on the assumed thermal boundary conditions. Consequently, the model must take into account the shaft and bush surfaces either isothermal or adiabatic. This work investigates the effect of such cases on the predictions of the pressure, temperature, locus, stiffness and damping coefficients on two and three lobed bearings. It shows that if both surfaces are isothermal, the lubricant temperature increase is smaller. If both surfaces are adiabatic, temperature increase is higher. The effect of lobe preload is also investigated, showing that the bearing coefficients increase with preload.